ON THE PROBLEM OF THE COMPONENT STRUCTURE OF ECOLOGICAL CONSCIOUSNESS OF THE FUTURE TEACHERS AND FACTORS THAT DETERMINE IT (Pedagogy of Higher and Secondary Education, 2006)
The structure of ecological consciousness of a teacher-to-be is revealed in the article. The author considers the components of ecological consciousness as well as the factors which determine the formation of those components.